PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MATEMATIS - Halawa, Nova Martilina; Lase, Sadiana; Zega, Yulisman; Telaumbanua, Yakin Niat (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2024)
One of the problems in learning mathematics at UPTD SMP Negeri 3 Gunungsitoli is that students' Mathematical Problem Solving Ability is still lacking. The purpose of this study was to determine the effect of the Guided Discovery Learning Model on the Mathematical Problem Solving Ability of UPTD SMP Negeri 3 Gunungsitoli Students. This type of research is experimental research using quantitative methods. This research was conducted at UPTD SMP Negeri 3 Gunungsitoli, with the research population being class IX in the 2023/2024 academic year. The research sample was taken by random sampling, the class that became the research sample was class IX-A as the experimental class, and class IX-B as the control class. The instrument used in this research is a written test in the form of a description test and consists of an initial test and a final test. The results of hypothesis testing, then obtained the value of tcount = 3.056 and the value of ttable = 2.004. Because thitung> ttabel or 3,056> 2,004, then Ho is rejected and Ha is accepted which means